Marketing Development Strategies for Mice Venue in The “New Normal” Era - Hemsuwan, Nithikittikarn; Jaroenwisan, Kaedsiri (Humanities and Social Sciences Journal of Pibulsongkram Rajabhat University, 2021)
Marketing development strategies for MICE venues in the New Normal era was conducted. The objectives of this research were to investigate market environment in the post COVID-19 era and present a market mix strategies. The data of this qualitative research was checked by Triangulation method and Narrative method. The data were collected through documentary method, focus group discussion, and in-depth interview. There were 15 samples selected by purposive sampling. The data were then analyzed by constant comparison. The results revealed that (1) according to the market environment in the post COVID-19 era for MICE venues, most problems were caused by external environment, for example, the uncertainty of COVID-19 pandemic affecting customer confidence, no concrete invention or manufacture of COVID-19 vaccines, and unclearness of public policies for problem-solving, management, and help for entrepreneurs. In addition, some problems were from internal environment such as shortage of personnel, lack of specific skills and several working skills, no knowledge and understanding of control system. According to four factors of organizational environment: strengths, weaknesses, opportunities, and threats, the strategies were determined for relationships at each level, namely organizational strategies, commercial strategies, and functional strategies. In terms of market mix strategies for MICE venues in New Normal era, it was found that the problems should explicitly be dealt with in order for customers to feel safe and comfortable. The rate of venue prices should also be reasonable for service standards. Moreover, venues should be convenient, spacious, and useful for activities, and they should be improved for ventilation, safety, and comfort.